Prevalence of sufficient levels of physical activity and associated factors in women - da Cruz Ramos de Araujo, Camila; Cardoso, Allana Alexandre; Tillmann, Ana Cristina; Pelegrini, Andreia; de Carvalho Souza Vieira, Melissa; Parcias, Silvia Rosane; Machado, Zenite; Coutinho de Azevedo Guimarães, Adriana (O Mundo da Saúde, 2016)
Physical activity is an important factor for a healthy life. Despite the benefits, most of the population does not meet the minimum recommendations. The objective of the study was to investigate the prevalence of sufficient physical activity and associated factors in women residing in Lages-SC. This cross-sectional descriptive study included a sample of 353 women between 20 and 59 years of age, according to a sample calculation based on the total population of women in this age group based on the Brazilian Institute of Geography and Statistics (IBGE). For the purposes of analysis, they were divided into three age groups: group 1 (20-33 years), group 2 (34-45 years) and group 3 (46-59 years). A self- administered questionnaire was used: A) personal identification; B) socioeconomic situation - Brazilian Association of Population Studies; C) International Physical Activity Questionnaire. The descriptive and inferential statistics were used through a two-way ANOVA followed by a Bonferroni’s Post Hoc test and a chi-square test. It was observed that approximately 70% of the women were considered sufficiently active, and a moderate intensity of physical activity was the most prevalent in all age groups, with a total of 76 min / day (p = 0.038); group 2 stood out in both categories. It is possible to report that the women of Lages meet the recommendation for the practice of physical activity, representing 70.4% in this study, and accumulate at least 30 daily minutes of moderate physical activity. These results may allow future comparisons and new reflections on the practice of physical activity and its benefits, mainly in the female population.